2022
DOI: 10.3389/fvets.2022.983562
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding transcriptomic profiles in the sheep mammary gland during different lactation periods

Abstract: Sheep milk production is a dynamic and multifactorial trait regulated by diverse biological mechanisms. To improve the quality and production of sheep milk, it is necessary to understand the underlying non-coding transcriptomic mechanisms. In this study, ribonucleic acid-sequencing (RNA-seq) was used to profile the expression of microRNAs (miRNAs) and circular RNAs (circRNAs) in the sheep mammary gland at three key lactation time points (perinatal period, PP; early lactation, EL; and peak lactation, PL). A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The expression of circRNAs has time-and tissue-specific characteristics. For example, circRNAs are differentially expressed in mammary gland tissues at different developmental stages, which has been confirmed in mammalian mammary gland tissues, such as that from goats [18], sheep [19,20], cattle [21,22], and mice [23], by transcriptome sequencing. In addition, the number of circRNAs in human glandular tissues (adrenal, mammary gland, pancreas, and thyroid), especially in the mammary gland (9665 candidate circRNAs), was higher than that in other adult tissues (colon, heart, kidney, liver, lung, and stomach) [24].…”
Section: Introductionmentioning
confidence: 81%
“…The expression of circRNAs has time-and tissue-specific characteristics. For example, circRNAs are differentially expressed in mammary gland tissues at different developmental stages, which has been confirmed in mammalian mammary gland tissues, such as that from goats [18], sheep [19,20], cattle [21,22], and mice [23], by transcriptome sequencing. In addition, the number of circRNAs in human glandular tissues (adrenal, mammary gland, pancreas, and thyroid), especially in the mammary gland (9665 candidate circRNAs), was higher than that in other adult tissues (colon, heart, kidney, liver, lung, and stomach) [24].…”
Section: Introductionmentioning
confidence: 81%
“…Liang et al [48] identified 216 ceRNAs, including 26 lncRNAs, 27 miRNAs, and 64 mRNAs, in human mesenchymal stem cell (MSC) adipose differentiation at 0, 3, and 6 d. The mRNAs in the ceRNA network were found to be mainly associated with glucose homeostasis and the response to insulin stimulation, as well as many lipid metabolism-related pathways, such as Ras, hypoxia-inducible factor-1 (HIF-1), PI3K-Akt, and insulin signaling. Chen et al constructed a ceRNA network using RNA-seq data and annotated potential candidate miRNAs and circRNAs involved in udder development in sheep, providing further insights into the influence of miRNAs and circRNAs on udder development in this species [49]. These studies not only identified many key molecular markers but also further demonstrated the integration of data from multiple sources for the construction of a global gene expression network, which could help us to understand the mechanisms underlying the formation of important traits [50].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Chen et al (2022) [ 61 ] investigated ncRNA profiles in Hu ewes’ mammary glands during different lactation periods (perinatal, 6 days postpartum, and 25 days postpartum) to understand their roles in mammary gland development and lactation. They identified several DE circRNAs: 348 in early lactation vs. perinatal, 373 in peak lactation vs. perinatal, and 36 in peak lactation vs. early lactation.…”
Section: Circular Rnas In Sheep: Shaping Health and Productivitymentioning
confidence: 99%